United Nations Psychology Day 2020 focused on Multilateralism - Priyadharshany Sandanapitchai; Harold Takooshian (Peoples' Friendship University of Russia (RUDN University), 2020)
As the United Nations marks its 75th anniversary in 2020, psychologists are increasingly involved in the work of the UN since 1945. This reached new heights on May 27, 2020, as the 13th annual Psychology Day at the United Nations drew a record attendance of 1,271 participants from 104 nations, to hear four international psychologists describe different aspects of their work on "multilateralism." This report offers a summary of the Day, including its four messages by Drs. Fathali Moghaddam, Susan Michie, Michele Gelfand, and Sarah Lyons-Padilla.